Contribution of Syaikh Muhammad Mahfuzh Al-Tarmasi in the Development of Intellectual-Spiritual Pesantren in Indonesia in the 20th Century - Dzulkifli Hadi Imawan (Santri: Journal of Pesantren and Fiqh Sosial, 2020)
This study will examine the contribution of Shaykh Muhammad Mahfuzh al-Tarmasi in the intellectual-spiritual development of Islamic boarding schools in Indonesia in the 20th century M. Shaykh Muhammad Mahfuzh al-Tarmasi who became one of the archipelago scholars who teach at the Haram Mosque was noted to have a major role in the development pesantren intellectual-spiritual in the archipelago in the 20th century AD Even though Indonesia at that time was still overshadowed by colonialism, but through its guidance to students in Mecca made a major contribution in improving the intellectual-spiritual boarding schools in the archipelago so that Indonesia was free from colonialism. Therefore, this research becomes important to know how the contribution of Shaykh Muhammad Mahfuzh al-Tarmasi in the intellectual-spiritual development in Indonesian pesantren in the 20th century AD. This study is a qualitative research with a historical approach. The results of this study stated that Shaykh Muhammad Mahfuzh al-Tarmasi contributed greatly to the development of the intellectual-spiritual boarding schools in Indonesia through his teaching to Indonesian students studying at the Haram Mosque and intensive coaching that combined fikriyah and ruhiyah to his students.